2019
DOI: 10.1371/journal.pone.0217886
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic motor cortex hyperexcitability in patients with chronic obstructive pulmonary disease

Abstract: Background and objectives Respiratory muscles dysfunction has been reported in COPD. Transcranial magnetic stimulation (TMS) has been used for assessing the respiratory corticospinal pathways particularly of diaphragm. We aimed to study the cortico-diaphragmatic motor system changes in COPD using TMS and to correlate the findings with the pulmonary function. Methods A case control study recruited 30 stable COPD from the outpatient respiratory clinic of Main Alexandria University hospital-Egypt and 17 healthy c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Elnemr, [27] and Eryuksel et al [28] reported that the measurement of the diaphragm thickening rate by ultrasound can accurately and quickly evaluate the diaphragm function. Brown et al [29] found that the mitochondrial density of type I muscle fibers in the diaphragm was higher than that of type II muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Elnemr, [27] and Eryuksel et al [28] reported that the measurement of the diaphragm thickening rate by ultrasound can accurately and quickly evaluate the diaphragm function. Brown et al [29] found that the mitochondrial density of type I muscle fibers in the diaphragm was higher than that of type II muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…3,44,48 The phrenic nerve undergoes myelin damage, with a slowing of the conduction velocity, with higher neuropathy values for subjects with hyperinflation and, in particular, for the left phrenic area. 48,49 Neuropathic adaptations correlate positively with FEV1. 49 Such neuropathy is a direct indicator of the risk of accidental falls.…”
Section: Effect Of Dynamic Hyperinflationmentioning
confidence: 99%
“…48,49 Neuropathic adaptations correlate positively with FEV1. 49 Such neuropathy is a direct indicator of the risk of accidental falls. 50…”
Section: Effect Of Dynamic Hyperinflationmentioning
confidence: 99%